An Inverse Method to Estimate Cowper‑Symonds Material Model Parameters from a Single Split Hopkinson Pressure Bar Test - Hernandez, Camilo; Blanco, David L.; Maranon, Alejandro (Springer Nature, 2023)
This paper presents the estimation of the parameters of the Cowper-Symonds material model of a commercial copper alloy from a single Split Hopkinson Pressure Bar Test using an inverse method. Parameters were identified by minimizing the error between the transmitted strain signal predicted by a finite element model and those observed experimentally. The Taylor Test was used to validate the identified parameters by comparing the experimental final length of impacted specimens and the ones predicted by a finite element model using the identified parameters. Also, identified parameters were contrasted with those found by a traditional curve-fitting approach. It was found that finite element models using the identified parameters are better able to predict plastic deformation than those using parameters from traditional curve-fitting.

Este artículo presenta la estimación de los parámetros del modelo de material Cowper-Symonds de una aleación de cobre comercial a partir de una prueba de presión de Hopkinson de una sola barra dividida utilizando un método inverso. Los parámetros se identificaron minimizando el error entre la señal de deformación transmitida predicha por un modelo de elementos finitos y las observadas experimentalmente. La prueba de Taylor se utilizó para validar los parámetros identificados comparando la longitud final experimental de las muestras impactadas y las predichas por un modelo de elementos finitos utilizando los parámetros identificados. Además, los parámetros identificados se contrastaron con los encontrados mediante un enfoque de ajuste de curvas tradicional. Se encontró que los modelos de elementos finitos que utilizan los parámetros identificados son más capaces de predecir la deformación plástica que los que utilizan parámetros del ajuste de curvas tradicional.
Keywords: UNS C83600; Mechanical characterization; High-strain rates; Split Hopkinson Pressure Bar Test; Taylor test; Inverse problem; Parameter identifcation